A Patient with Systemic Lupus Erythematosus Complicated by Neurological Symptoms of Toluene Poisoning. (15th July 2013) - Isoda, Kentaro; Takeuchi, Tohru; Makino, Shigeki; Hanafusa, Toshiaki
Abstract : We report a patient with systemic lupus erythematosus complicated by toluene poisoning. She had erythema, alopecia, arthralgia, and various neurological symptoms. Laboratory findings showed leukocytopenia, low levels of complements, and anti-dsDNA antibody. However, normal interleukin-6 level and IgG index of cerebrospinal fluid and brain magnetic resonance imaging and single photon emission computed tomography findings suggested that her neurological symptoms were caused by metabolic disorder but not neuropsychiatric systemic lupus erythematosus. Erythema, alopecia, and arthralgia improved rapidly after administration of prednisolone and tacrolimus, whereas neurological symptoms improved only gradually. Because of a history of exposure to toluene, her neurological symptoms were considered to be due to toluene poisoning. The differentiation of toluene poisoning from neuropsychiatric systemic lupus erythematosus based on symptoms is difficult because both induce various neuropsychiatric disorders. Laboratory findings of cerebrospinal fluid, radiological findings, and medical interview were useful for differentiation of toluene poisoning from neuropsychiatric systemic lupus erythematosus.